Prefabricated Envelope Green Remodeling Potential of Public Office Buildings in Korea - Oh, Ji Hyun; Kim, Sun Sook (Buildings, 2024)
The public sector should reduce energy consumption and carbon emissions from the building stock, thereby serving as a role model for the private sector. In Korea, public buildings are leading the green remodeling business initiative as part of a carbon-neutral strategy. Building envelope retrofitting is essential for the green remodeling of existing buildings because it significantly affects the buildings’ aesthetic appearance, occupant comfort, and energy usage. From the perspectives of constructability and cost, prefabricated envelope systems offer various advantages and can contribute to the growth of the green remodeling business. To develop an effective prefabricated envelope system, a thorough analysis of the existing building stock must be conducted. Therefore, this study aims to investigate existing public office buildings in Korea to obtain a better understanding of the considerations necessary for developing prefabricated envelope systems. The survey utilized the image search and road-view functions of map services, following an appropriate sample design. Based on the survey results, the characteristics of the building types and envelopes, as well as considerations for developing prefabricated envelope systems are discussed. Furthermore, this study quantitatively analyzed the energy conservation potential through building energy simulations.
Keywords: Building envelopes; Building stocks; Carbon emissions; Energy efficiency retrofit; Green remodeling prefabricated envelope system; Private sectors; Public offices; Public sector; Reduce energy consumption; Role model; building envelope; energy efficiency retrofit; green remodeling prefabricated envelope system; public office